Augmentation of major isoflavones in Glycine max L. through elicitor mediated approach - Saini, Ramesh K; Akitha Devi, Muthu K; Parvatam, Giridhar; Ravishankar, Gokare A (Acta Botanica Croatica, 2013)
Isoflavone content in soybean seeds was enhanced by the elicitor-mediated approachunder field conditions through the floral application of abiotic elicitors-salicylicacid, methyl jasmonate and biotic elicitors-Aspergillus niger and Rhizopus oligosporus. Among isoflavones, daidzein and glycitein were found to be highly responsive to elicitors,with an increase of 53.7% and 78.7%, respectively as compared to control. Highest totalisoflavone content (1276.4 mg g–1 of seeds) was observed upon the administration of 0.1mM salicylic acid, which is 92.7% higher than in control. This study would be valuable for augmentation of the isoflavone content in soybean seeds in field grown plants for better nutraceutical potential.